Macroprudential Indicators of Financial System Soundness - Hilbers, Paul (Occasional Papers; Occasional Paper ;, 2000)
Following the severe financial crises of the 1990s, identifying and assessing financial sector vulnerabilities has become a key priority of the international community. The costly disruptions in global markets underscored the need to establish a set of monitorable variables for evaluating strengths and weaknesses in financial institutions and to alert authorities of impending problems. These variables, indicators, of financial system health and stability known collectively as macroprudential indicators, are the subject of this Occasional Paper by the Monetary and Exchange Affairs Department and the Statistics Department. Macroprudential indicators take measures at both the level of aggregated financial institutions and at the macroeconomic level; financial crises often occur when weaknesses are identified in both. The authors provide a breakdown and explanations of these indicators and a review of the theoretical and empirical work done thus far. Work at other international and multilateral institutions is included as well as the experiences of several national central banks and supervisory agencies. This paper provides a valuable reference source of current knowledge about macroprudential indicators and issues related to their analysis, identification, measurement, and possible dissemination.